Kepuasan Penumpang Terhadap Aplikasi Travelin di Bandara Internasional Banyuwangi - Nandana Abiyyu Rasendriya Putra; Teguh Ariebowo (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to assess passenger satisfaction with the Travelin application at Banyuwangi International Airport. Developed by PT Angkasa Pura II, the app offers features such as TravelinPass, a biometric-based electronic boarding system. Although implemented, many passengers are still unfamiliar with its optimal use. A quantitative approach was applied using surveys distributed to 196 users. The questionnaire was based on five satisfaction indicators: expectation, performance, comparison, experience, and confirmation. The results showed an overall satisfaction score of 2.37 on a 1–4 Likert scale, indicating a “low satisfaction” category. Key issues include limited user knowledge and underperformance of services. These findings highlight the need for improved user education, feature enhancements, and user interface development to maximize the app’s benefits for passengers.